2014
DOI: 10.3892/mmr.2014.3063
|View full text |Cite
|
Sign up to set email alerts
|

Janus kinase/signal transducer and activator of transcription inhibitors enhance the protective effect mediated by tanshinone IIA from hypoxic/ischemic injury in cardiac myocytes

Abstract: Tanshinone IIA is a lipophilic abietane diterpene compound, which exhibits protective effects against ischaemia/reperfusion injury; however, the pathways responsible for the myocardial protective activities of tanshinone IIA remain to be elucidated. The aim of the present study was to investigate the effect of tanshinone IIA on the Janus‑activated kinase (JAK)/signal transducer and activator of transcription (STAT) signaling pathway, which is associated with cardiac dysfunction during ischemia/reperfusion. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
2
4
0
Order By: Relevance
“…These results suggest that JAK2/STAT3 activation is involved in multiple HG-stimulated injuries. Our results are supported by several recent reports [ 31 33 ]. Previous research has found that AG490 exerts anti-inflammatory effects [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that JAK2/STAT3 activation is involved in multiple HG-stimulated injuries. Our results are supported by several recent reports [ 31 33 ]. Previous research has found that AG490 exerts anti-inflammatory effects [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study has also demonstrated that TIIA (3 M) reduced hypoxia induced late apoptosis in H9C2 cells, the effect linked to decreasing hypoxia inducible factor-1 (HIF-1 ) translocation, balancing in Bcl-2/Bax ratio, reducing cytochrome c release and caspase 3 activity [36]. A recent study also found that the protection by TIIA on hypoxic ischemia-induced injury could be enhanced by the JAK2/STAT3 inhibitors [87]. Additionally, the antiapoptosis effects of TIIA were associated with regulation of intracellular calcium, ATP, mitochondrial superoxide, and SOD levels but not intracellular H 2 O 2 [35].…”
Section: Effects Of Tanshinones On Ischemia Reperfusion Injuriessupporting
confidence: 64%
“…[30][31][32] Its protective mechanisms have been broadly investigated. Several reports reveal the inhibited effect of TSA on ERS.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested TSA is a plentiful lipophilic abietane diterpene element which was separated from Danshen (Salvia miltiorrhiza), a Traditional Chinese Medicine usually utilized for therapy of cardiovascular diseases. [30][31][32] Its protective mechanisms have been broadly investigated. Several reports reveal the inhibited effect of TSA on ERS.…”
Section: Discussionmentioning
confidence: 99%